PERCEIVED IMPACT OF CULTURAL TOURISM AMONG THE RESIDENTS: FOCUSING ON RUWATAN DREADLOCKS CHILDREN IN DIENG KULON VILLAGE - Sahid Sahid; M. Elfan Kaukab (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2020)
Dieng Kulon village is one of the villages which is located in Dieng Plateau Area, Banjarnegara regency. There is a tradition of ruwatan ritual procession that has been done by the residents since hundred years ago. The ruwatan then becomes the cultural tourism. This study aims at exploring the perceived impact of cultural tourism among the residents in Dieng Kulon village. Participant observation and in-depth interview are conducted to local residents in Dieng Kulon village and governmental officials who manage the tourism sector in the regency of Banjarnegara. The data is then comprehensively analyzed using descriptive qualitative method. The result of this study shows that based on the residents` perception, the presence of dreadlocks children bring the “berkah” or prosperity. The dreadlocks children in Dieng have the distinct characteristics, they have to conduct the ritual procession of ruwatan hair cutting. Some residents agree for projecting the public ruwatan into cultural tourism on the reason of cultural preservation while others do not agree because they worry about the decrease of sacredness and cultural value of that tradition. The subsistence of them also gradually change into the tourism activity.